Effectiveness of Added L-Ascorbyl Palmitate Antioxidant Synthezed Enzymatically in Coconut Oil - Sutarno Sutarno; Yateman Arriyanto; Arief Budyantoro (Jurnal ILMU DASAR, 2009)
Research on effect of NaOH/Coal Fly Ash ratio in faujasite synthesis to faujasite crystallinity has been conducted. Faujasite synthesis has been conducted by destructed coal fly ash using sodium hidroxide (NaOH) with NaOH/Coal Fly Ash ratio = 1.0;1.2; 1.5; 2.0; 2.5 and 3.0 (w/w) on the solid phase. The solid mixtures cured at 550 oC for 1 h and followed by coolling process. Addition of distilled water to the solid mixtures and agitation for 24 h were done until we have slurry. The slurry kept on bomb autoclave and hydrothermal reaction has done at 100 oC for 72 h. The solid products are dried on oven and characterized using XRD. Al and Si were analyzed using UV-Vis spectroscopy method. The Faujasite has been produced by this research using of NaOH/Coal Fly Ash ratio ranging from 1 to 1.5 ratios (w/w). The range of NaOH/Coal Fly Ash ratio from 2 to 3 ratio (w/w) gave hidroxysodalite as hydrothermal product. The best ratio was by 1,2 NaOH/Coal Fly Ash ratio (w/w), it showed the highest crystallinity of faujasite and Si/Al ratio of Faujasite was higher than others. This research concluded that the high concentration of OH- on the hydrothermal system can transform faujasite to hydroxysodalite.